PP.LB01.17: FIRST STEPS TO DEVELOP A CARDIOVASCULAR RISK ASSESSMENT EQUATION IN SPANISH YOUNG, WORKING POPULATION. THE IBERSCORE PROJECT. (June 2015) - Cabrera, M; Calvo-Bonacho, E.; Catalina-Romero, C.; Quevedo-Aguado, L.; Fernández-Labandera, C.; Ruilope, L.M.; Sánchez-Chaparro, M.A.; Valdivielso, P.
Abstract : Objective: To compare cardiovascular risk factors (CVRF) and SCORE charts, in workers who experienced or not a first cardiovascular event. Design and method: This prospective study was part of the IBERSCORE project, aimed to develop a CVR predictive equation in Spanish working population. 5-years follow-up was carried-out in a cohort of 627, 253 workers, selected between 2004–2006, without prior cardiovascular disease. Demographic, anthropometric, cardiovascular, work-related risk factors, information about treatments, and blood samples were recorded. CVR was stratified according to the SCORE model and the current Joint European Societies' guidelines (JESG) on cardiovascular disease prevention and the prevalence of CVRF. Episodes of sick leave for cardiovascular events and fatal events were also registered, during follow-up. Results: 71.7% of participants were men (mean age 35.7 ± 10.7 years). 5.5% of subjects had high CVR (n = 30, 125). Prevalences of workers with CVRF were: smoking (48.9%); hypertension (21.0%); type 2 (1.0%) or type 1 (0.3%) diabetes; metabolic syndrome (8.0%); atherogenic dyslipidemia (5.4%). An average prevalence of 15.7% (SD = 16.7) for sedentary work, 6.6% (SD = 9) for shift work, and an average score of 60.4 (SD = 3.4) in a psychosocial score (0–100 points), were also estimated. Over five years 1, 785 workers (0.3%) suffered a cardiovascular event (1, 080 coronary heart diseases, 471 cerebrovascular diseases, 185 peripheral artery diseases, 49 heart failures). 10 of those events (0.6%) were fatal. According to current JESG on cardiovascular disease prevention, the distribution by CVR levels was: 16.1% very high (260); 12.0 % high (192); 41.0 % moderate (660); 31.0% low (500). From those with low CVR, 62 (3.5%) had a relative risk >4. SCORE >=5% affected 13.3% of the subjects with cardiovascular event. Conclusions: As expected, the incidence of CV events in our cohort was low. Estimated high or very high CVR was present in a low percentage of workers when they really suffered CV events. There is an urgent need of more specific tools focussing on the particular risk profile of the working population (e.g. younger age or exposure to psychosocial risk factors at work).